2018
DOI: 10.1111/pce.13407
|View full text |Cite
|
Sign up to set email alerts
|

Metabotype variation in a field population of tansy plants influences aphid host selection

Abstract: It is well known that plant volatiles influence herbivores in their selection of a host plant; however, less is known about how the nonvolatile metabolome affects herbivore host selection. Metabolic diversity between intraspecific plants can be characterized using non-targeted mass spectrometry that gives us a snapshot overview of all metabolic processes occurring within a plant at a particular time. Here, we show that non-targeted metabolomics can be used to reveal links between intraspecific chemical diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 70 publications
2
66
1
Order By: Relevance
“…Our previous work showed that neither the plant volatile chemotypes nor the metabotypes studied here were likely induced by aphid feeding (Clancy et al, 2018(Clancy et al, , 2016 and Host preference of aphids to different plant variants is known from various experimental studies .…”
Section: Direct Effects Of Plant Chemical Variationmentioning
confidence: 70%
See 4 more Smart Citations
“…Our previous work showed that neither the plant volatile chemotypes nor the metabotypes studied here were likely induced by aphid feeding (Clancy et al, 2018(Clancy et al, , 2016 and Host preference of aphids to different plant variants is known from various experimental studies .…”
Section: Direct Effects Of Plant Chemical Variationmentioning
confidence: 70%
“…The lack of association between plant metabotypes and aphid genotypes in the very first sampling period in 2015, but significant associations in all the later three periods, highlights the role of plant secondary metabolites on aphid performance, with high population growth rates leading to longer colony persistence (Senft et al, 2017), and stronger genotype-metabotype associations. We previously showed that aphids colonised "preferred" volatile chemotypes in the early part of the season (Clancy et al, 2016) and later on colonised almost all plants belonging to the "preferred" metabotypes irrespective of which volatile chemotypes they belonged (Clancy et al, 2018).…”
Section: Direct Effects Of Plant Chemical Variationmentioning
confidence: 99%
See 3 more Smart Citations